Community Service Based on National Defense: Post-Flood Health Recovery Interventions in Aceh: Pengabdian Masyarakat Berbasis Bela Negara: Intervensi Pemulihan Kesehatan Pascabencana Banjir di Aceh - Rika Yuliwulandari; Aristanto Prambudi; Fitri Sepviyanti Sumardi; Fachrizal A. Prawiragara Fairuz; Haniyah Ramadhani; Raihan Mahesa Ardiansyah; Zulfan Febriawan (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2026)
The post-flood disaster in Aceh caused significant disruption to essential health services, an increase in injury-related cases, worsening environmental sanitation, and treatment interruption among patients with chronic diseases. This community service program, based on the spirit of national defense (bela negara), aimed to strengthen post-disaster health recovery through integrated medical interventions and the application of innovative health technologies. Activities were carried out in collaboration with the Puskesmas Meureudu, the Aceh local government, and community stakeholders. The intervention included the deployment of the Emergency Minor Surgery Box (EMSB) and Portable Wound Care Kit (PWCK) for managing lacerations, puncture wounds, abrasions, and infections. Chronic disease services were restored through the provision of essential medications and portable vital monitoring tools. Health promotion efforts included hygiene education, disaster preparedness training, and the use of Mobile Handwashing Stations to support infection prevention in high-risk environments. The program also implemented portable sterilization technology to ensure safe reuse of medical instruments in resource-limited settings. Capacity-building activities were provided for healthcare workers and community cadres to ensure continuity and sustainability of services. The results demonstrated improved wound care management, better continuity of chronic disease treatment, enhanced community sanitation practices, and increased readiness of health workers in disaster response. The program successfully strengthened the local health system and created a sustainable model for post-disaster health recovery through technology transfer and cross-sector collaboration.